The Influence of Financial Technology and Financial Literacy on Financial Behavior in the Digital Era - Rasyid, Nugraha; Goso, Goso; Ikbal, Muhammad (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study was conducted to determine the effect of financial technology and financial literacy on the financial behavior of the Sukamaju village community. Data were collected by distributing questionnaires through Google Form media using a Likert scale. was the population in this study millennial generation aged 19-39 years. The variables used in this study were financial technology and financial literacy as independent variables and financial behavior as the dependent variable. This study approach by uses a quantitative collecting primary data. The sampling technique used in this study used the Slovin formula with a 10% margin of error so. that the number of samples determined was 100 respondents The data analysis technique used was to test the quality of primary data with validity and reliability tests, followed by multiple linear regression analysis with determination coefficient tests, partial and simultaneous significant tests using SPSS 25. Based on financial behavior the financial literacy results, partially affects financial behavior, simultaneously financial technology and financial literacy affect the financial of the analysis and discussion using multiple linear regression, it was concluded that partially financial technology affects behavior of the millennial generation of Sukamaju village.